Impact of Yoga on Anxiety in Pregnant Women in the Era of the COVID-19 Pandemic: A Literature Review - Mukarromah, Nur; Dewi, Arum Puspita; Marini, Gita; Aisyah, Siti; Priyantini, Diah (Universitas Muhammadiyah Surabaya, 2022)
Background: Pregnancy in the era of the 2019 Coronavirus Disease (COVID-19) pandemic can cause anxiety for pregnant women. Pregnant women often experience anxiety during pregnancy which can trigger various disorders during pregnancy. Yoga movements can reduce the level of anxiety in pregnant women. Objective: To determine the impact of yoga on anxiety in pregnant women in the era of the Covid 19 pandemic. Method: Literature review of Yoga journals on anxiety in pregnant women. Search for articles via the internet with the PNRI database:, Sciendirect, DOAJ and Google Scholar. The review was carried out on 10 articles on Yoga on anxiety in pregnant women, starting in 2019-2021, 7 articles in Indonesian and 3 in English, full text discussing Yoga anxiety in pregnant women, then synthesized using tables. Results: Yoga during the Covid 19 pandemic era which is carried out gradually can reduce anxiety in pregnant women. Conclusion: Yoga identification can have an impact on anxiety in pregnant women in the era of the Covid-19 pandemic, there is information and a comprehensive picture of yoga interventions. It is hoped that health workers can provide knowledge or counseling to pregnant women to help reduce anxiety levels with yoga.